Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I am currently trying to prove the following relationship $$1 + r \leq \left(1 +\frac{r}{m}\right)^m\quad \text{for any }m \geq 1.$$

Would you be so kind and provide some hints/solutions to the above?

share|improve this question
2  
You might study the function $f(x) = e^{x \ln \left(1+\frac{r}{x}\right)}$. –  Joel Cohen Apr 23 '12 at 20:56
4  
This is simply Bernoulli Inequality –  TenaliRaman Apr 23 '12 at 21:19
add comment

3 Answers 3

up vote 4 down vote accepted

You'll probably want to assume at least $r \ge -m$, otherwise it can be false (e.g. try $m=3$ and $r < -9$).

Let $f(r) = (1+r/m)^m - (1+r)$ for $-m \le r < \infty$. Then $f(0) = f'(0) = 0$, while $f''(r) = \frac{m-1}{m} (1+r/m)^{m-2} \ge 0$, so $f(r)$ is convex on this interval. Therefore $f(r) \ge 0$ there.

share|improve this answer
    
+1 that's nice $$ –  draks ... Apr 23 '12 at 21:08
    
It might be the hangover, but $m=4,r=-12$ gives $1-12=-11\leq\left(1-\dfrac{12}{4}\right)^4=16$ which is true. –  Asaf Karagila Apr 24 '12 at 6:25
    
@AsafKaragila: Of course the inequality is true when $r \le -1$ and $m$ is an even integer (left side $\le 0 \le$ right side). It is false if $m$ is an odd integer $\ge 3$ and $r < -3m$, and it is meaningless if $r < -m$ for most non-integers $m$. –  Robert Israel Apr 24 '12 at 6:59
    
So it is the hangover! :-) –  Asaf Karagila Apr 24 '12 at 7:12
add comment

This is not a very nice solution, but for $m$ not an integer:

It is easy to see that $\frac{\log(1+x)}{x}$ times a constant is a decreasing function (simply because $(\log(1+x)≤ x)$ and x grows faster). Hence for $x=\frac{r}{m}$ the function $$ m*\log(1+r/m) $$ is increasing for increasing $m≥1$. But therefore so is the function $(1+\frac{r}{m})^m$.

share|improve this answer
add comment
  1. If you do not know $\left(a+b\right)^n=\sum_{i=0}^n\binom{n}{i}a^ib^{n-i}$, prove it by induction using $\binom{n}{k}=\binom{n-1}{k}+\binom{n-1}{k-1}$.

  2. Note that $\binom{m}{0}=1$, $\binom{m}{1}=m$ for every $m$, and use it to prove the inequality.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.